Sebuah PENGARUH KONSELING MELALUI MEDIA SOSIAL TERHADAP PENGETAHUAN DAN PRAKTIK PENGELOLAAN HIPERTENSI: Pengaruh Konseling Melalui Media Sosial Terhadap Pengetahuan Dan Praktik Pengelolaan Hipertensi - Rina Mitasari; Heryudarini Harahap; Sri Desfita (Jurnal Kesehatan Komunitas, 2019)
Hypertension as one of the "comorbidity" of heart disease, the prevelance was in Indonesia. Efforts to manage hypertension by health promotion conducted health workers in Clinics is rarely done because of the health officers focus more curative ketindakan so lack of preventative and promotif. The purpose of the study was to know the influence of counselling through social media to knowledge and practice of the management of hypertension. The research was conducted in July to August 2018. This study was quantitative using Non Randomized Experiments Quasy design Control Group Pretest Postest. Analysis of the data in the data analysis did knowledge and practices before and after the intervention was performed. The sample in this research is 52 people with consecutive sampling techniques. The analysis of the data used, namely the test of paired t test and independent t test.. The study showed that are obtained namely higher average variable knowledge on social media group compared to the conventional group. There was no difference in average which means the practice of managing hypertension or pre-posttest score on the conventional group and the Group of social media. This research was a great alternative of health education in health promotion programmes to enhance knowledge in managing hypertension disease independently one to control high blood pressure.